[PP.27.26] FIRST MEDICAL WARNING.A REAL HARAKIRI. HYPERTENSIONOLOGIST'S HYPERTENSION. SAGLIKER EFFECT. CLASSICAL MANUAL BP MEASUREMENTS MUST BE BANNED BY LEGISLATIONS AND ESH AND WHO. (September 2016) - Sagliker, H.S.; Sagliker, Y.; Paylar, N.; Sagliker, C.; Ozkaynak, P. Sagliker; Ocal, F.; Inal, T.; Kolasin, P.; Balal, M.
Abstract : Objective: It is known some normals and hypertensives get higher BP when facing medical environments or devices. Effect called WCE, WCH, stress hypertension or office hypertension. We examined if same be also found in medical staff in outpatient clinics. This is first medical definite findings in medicine on subject. Figure. No caption available. Design and method: 58 doctors examined 12 hypertensives by measuring BP in person, per se with classical manual recorders, every 10 minutes for two hours first day, then relaxed consecutive day, similarly two hours. SBP, DBP, MAP, HR, two hours NE, E, VMA, metanephrine in urines and plasma NE, E, PRA, A and A II examined. Additionally plasma AT II levels examined just before BP recordings in first stress day. Results: SBP, DBP, MAP, HR, cathecolamins in two-hours urines, blood cathecolamins PRA, A decreased from first day to second. Interestingly plasma AII decreased from time of prerecordings to time of postrecordings in first stres day. P values for differences were less than 0, 001. Conclusions: Personels had higher SBP, DBP, MAP, HR, PRA and A, cathecolamins in urines and plasma after examinations. Reduction of AII at time of postrecordings be explained by AII's short half life. If AII be examined continously during measurements, could be found higher at first but decreasing tremendously by time till end-point. Staff could face complications such as cerebrovascular attacks, myocardial infarctions, blindness if they have hypertension or prone to it due to some present abnormalities in the body. Manual recordings for personel was a reverse white coat effect plus hand grip exercise test and dangerous. In developping countries as Turkey, India, Pakistan, Bengladesh, China, Endonesia, Maleysia where 150–200 patients examined and BP recorded daily only by one doctor, manual recorders be banned by legistlations and started first in history via ESHand WHO. This is a sine qua non humanity task.